Long‐term Outcome of Irish Wolfhound Dogs with Preclinical Cardiomyopathy, Atrial Fibrillation, or Both Treated with Pimobendan, Benazepril Hydrochloride, or Methyldigoxin Monotherapy. (3rd March 2016) - Vollmar, A.C.; Fox, P.R.
Abstract : Background: Dilated cardiomyopathy (DCM) is a common cause of morbidity and mortality in the Irish Wolfhound (IW). However, the benefit of medical treatment in IW dogs with preclinical DCM, atrial fibrillation (AF), or both has not been demonstrated. Objectives: Compare the time to develop congestive heart failure (CHF) or sudden death in IW dogs with preclinical DCM, AF, or both receiving monotherapy with pimobendan, methyldigoxin, or benazepril hydrochloride. Animals: Seventy‐five client‐owned IW dogs. Methods: Irish Wolfhound dogs were prospectively randomized to receive pimobendan (Vetmedin ® )®, benazepril HCl (Fortekor ® )2, or methyldigoxin (Lanitop ® )3 monotherapy in a 1:1:1 ratio in a blinded clinical trial. The prospectively defined composite primary endpoint was onset of CHF or sudden death. To assure stringent evaluation of treatment effect, data from dogs complying with the study protocol were analyzed. Results: Sixty‐six IW fulfilling the study protocol included 39 males, 27 females; median (interquartile range) age, 4.0 years (3.0–5.0 years) and weight, 70.0 kg (63.0–75.0 kg). Primary endpoint was reached in 5 of 23 (21.7%) IW receiving pimobendan, 11 of 22 (50.0%) receiving benazepril HCl, and 9 of 21 (42.9%) receiving methyldigoxin. Median time to primary endpoint was significantly longer for pimobendan (1, 991 days; 65.4 months) compared to methyldigoxin (1, 263 days; 41.5 months; P = .031) or benazepril HCl‐(997 days; 32.8 months; P = .008) treated dogs. Conclusions and Clinical Importance: In IW dogs with preclinical DCM, AF or both, pimobendan monotherapy significantly prolonged time to onset of CHF or sudden death than did monotherapy with benazepril HCl or methyldigoxin.